2018
DOI: 10.2337/dc17-2396
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Distress and Glycemic Control: The Buffering Effect of Autonomy Support From Important Family Members and Friends

Abstract: Autonomy support from main health supporters may contribute to better glycemic control by ameliorating the effects of diabetes distress. Interventions that reduce diabetes distress and enhance the autonomy supportiveness of informal supporters may be effective approaches to improving glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 41 publications
7
70
0
Order By: Relevance
“…Sharing problems with friends and family members was the most common strategy adopted. This is similar to the findings reported in previous studies where participants reported increased need to talk with someone to vent out their distress [30].…”
Section: Discussionsupporting
confidence: 91%
“…Sharing problems with friends and family members was the most common strategy adopted. This is similar to the findings reported in previous studies where participants reported increased need to talk with someone to vent out their distress [30].…”
Section: Discussionsupporting
confidence: 91%
“…Sharing problems with friends and family members was the most common strategy adopted. This is similar to the ndings reported in previous studies where participants reported increased felt need to talk with someone to vent out their distress [25].…”
Section: Discussionsupporting
confidence: 91%
“…Family members and peers are an underutilized resource for ongoing support and often struggle with how to best provide help (47,48). Including family members in the DSMES process can help facilitate their involvement (49)(50)(51). Such support people can be especially helpful and serve as cultural navigators in health care systems and as liaisons to the community (52).…”
Section: Social Determinants Of Health (1183)mentioning
confidence: 99%